Open and endovascular repair of aneurysms affecting the distal extracranial internal carotid artery: case series. (4th August 2016) - Mukherjee, P; Huilgol, R; Graham, A; Fagan, P
Abstract: Objective: Three cases of internal carotid artery aneurysm affecting the distal cervical segment were retrospectively reviewed. Methods: Two patients underwent open surgical repair requiring petrous segment exposure for bypass of the affected segment using a Fisch type A lateral skull base approach. The third patient underwent endovascular stenting. Results: There were no cerebrovascular complications post-operatively. Both open repair patients experienced temporary lower cranial nerve palsies. One required facial nerve grafting. All patients had patent grafts at follow up. The stent graft patient had a small endoleak at six months. Conclusion: Endovascular and open approaches both have advantages and disadvantages. Treatment needs to be tailored to the lesion and the patient. An open surgical approach is difficult but well established. Endovascular treatment of these lesions is a relatively recent technique, and new cases need to be continually reported with a view to attaining long-term data.